ALOMORF NASALISASI DAN NASAL PENAMBAH DALAM BAHASA BIDAYUH-SOMU - Bunau, Eusabinus (Universitas Tanjungpura, 2017)
AbstractÂ This is a research on linguistics field, that is Nasalization Process of Bidayuh-Somu language. Nasalization is is a process of affixation as one of word formation processes. The Nasalization is one of processes to derive verb, that is transitive verb. Result of the research shows, the Nasalization Process in the Bidayuh-Somu language is applied through affixation of Nasalization morpheme and its variants comprising allomorphs and homorganic nasals to root word. Analysis on structure shows, Nasalization in the Bidayuh-Somu langauge applies by replacing and/or adding root word with the allomorphs and homorganic nasals. Therefore, the Nasalization in the Bidayuh-Somu language functions both as class-maintaining and class-changing. As class-maintaining, the Nasalization is prefixed to root word that is verbal. Meanwhile as class-changing, the Nasalization in this Bidayuh-Somu language is prefixed to root word that is nominal. Besides, it was also found out that the Nasalization is functioned to derive active verb, that is transitive verb.Â Keywords: Nasalization Process, Morpheme and Nasalization Allomorph, Repalcive and Additive Nasalization.